The Korean Society for Biomaterials joins forces with BioMed Central - Noh, Insup (Biomater Res, 2014)
It is my pleasure to usher in a new era for Biomaterials Research in 2014: gold open access. The journal has a long history of publishing research across the broad spectrum of biomedical materials. Supported by the Korea Research Foundation, it was founded in 1996 as the official journal of the Korean Society for Biomaterials. Biomaterials Research now joins BioMed Central’s portfolio of open access journals.